Derecognition and symbolic demarcation in domestic labor: moral progress put to the test - Garcia de Mello, Luciana; Rosenfield, Cinara L. (SOCIOLOGIAS, 2024)
This article analyzes domestic labor in Brazil by contrasting recent legal advances that made labor rights of domestic workers equal those of the other workers with the persistent culture of derecognition and denial of rights. To this end, the analysis draws on the theory of recognition as postulated by Axel Honneth as well as on data from empirical research that examined narratives by domestic workers extracted from a Facebook page, which were posted between 2016 and 2022. The aim is to empirically demonstrate the relevance of the concept of derecognition in its different forms, by exploring the moral grammar of social conflict in the concrete case of domestic workers’ experiences. The analysis distinguishes three negative practices of recognition – or derecognition: a) the inability to recognize what the subject considers worthy of recognition; b) distorted or ideological recognition; c) the denial of recognition. It becomes clear that the achievement of normative rights does not suffice to overturn moral contempt. In the daily lives of domestic workers, institutionalized relations of recognition break down, limiting the scope of legal recognition.